Osteocalcin As A Marker Of Bone Metabolism Disorders In Children With Juvenile Idiopathic Arthritis - Dinmukhammadieva Dilorom Rakhimdjanovna; Shadiyeva Soadat Ulmasovna (Genius Journals, 2025)
To determine the relationship between osteocalcin and markers of inflammation and bone metabolism in children with juvenile idiopathic arthritis (JIA).
Keywords: children; juvenile; relationship